Judges Considerations in Canceling Polygamous Marriages in Religious Courts - Yuliatin, Yuliatin (Al-Risalah, 2022)
Polygamy is allowed in Indonesia, providing the act is justified by religion and the rules of marriage law. A husband who wants to have more than one wife must fulfil various requirements of the Court. Based on the principle of “audi alteram partem,” the Supreme Court panel assesses the consideration of the Jambi Provincial Religious High Court against the answers, evidence, and witnesses presented by the defendant. This is to ensure the right decision is made, though the case was submitted late and no trial was filed. This research found that the Supreme Court deems a polygamy permit compulsory and aims to protect the welfare of the parties bound in the marriage. The word “can” in The Compilation of Islamic Law (KHI) article 71A showed that a marriage annulled due to polygamy without court permission is tentative or facultative. This indicated an annulment application must be submitted to the Court and the final decision is dependent on the assessment of the benefit of the wife and/or children. The legal consequence, based on the decision of the Religious Court to accept the marriage itsbat and the refusal to cancel the marriage bond, is that the children of the second wife will receive inheritance rights from the father, including property obtained with the first wife.